Improving cell disruption efficiency to facilitate protein release from microalgae using chemical and mechanical integrated method - Phong, Win Nee; Show, Pau Loke; Le, Cheng Foh; Tao, Yang; Chang, Jo-Shu; Ling, Tau Chuan (Elsevier, 2018)
One of the critical challenges in releasing protein from microalgae is to effectively disrupt their rigid thick cell walls. This study could provide some guidance on the implementation of a simple, cost-effective and scalable cell disruption in a downstream processing of microalgal industry for the recovery of protein from microalgae. The effects of solvent types, alkalis, and ultrasonication in disrupting microalgal cell wall and protein solubility were studied. It was found that alkaline treatment played a key role in cell disruption and protein solubilisation. From the industrial perspective, water is an excellent choice of extractive solvent due to low-cost, safety, and scalability. Among all the tested methods, the combination of both alkaline and ultrasonication treatment demonstrated the greatest cell disruption efficiency and was thus suggested to be use at large scale.